Inspired by Paul Patawaran

Algebra Level pending

4 b 2 16 b + 4 = 0 \large 4b^2 -16b + 4 = 0

Given that positive real b b satisfies the equation above, find the value of ( b 6 + b 5 ) ( 1 b 11 + 1 ) \left(b^6 + b^5\right)\left(\dfrac{1}{b^{11}} + 1\right) without finding the value of b b .

1256 3358 2456 3426

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

4 b 2 16 b + 4 = 0 Dividing both sides by 4 b 2 4 b + 1 = 0 Dividing both sides by b b 4 + 1 b = 0 Rearranging b + 1 b = 4 ( b + 1 b ) 2 = 4 2 b 2 + 2 + 1 b 2 = 16 b 2 + 1 b 2 = 14 ( b + 1 b ) ( b 2 + 1 b 2 ) = 4 × 14 b 3 + b + 1 b + 1 b 3 = 56 b 3 + 4 + 1 b 3 = 56 b 3 + 1 b 3 = 52 ( b 2 + 1 b 2 ) ( b 3 + 1 b 3 ) = 14 × 52 b 5 + b + 1 b + 1 b 5 = 728 b 5 + 4 + 1 b 5 = 728 b 5 + 1 b 5 = 724 ( b 3 + 1 b 3 ) 2 = 5 2 2 b 6 + 2 + 1 b 6 = 2704 b 6 + 1 b 6 = 2702 \begin{aligned} 4b^2 - 16b + 4 & = 0 & \small \color{#3D99F6} \text{Dividing both sides by }4 \\ b^2 - 4b + 1 & = 0 & \small \color{#3D99F6} \text{Dividing both sides by }b \\ b - 4 + \frac 1b & = 0 & \small \color{#3D99F6} \text{Rearranging} \\ \implies \color{#3D99F6} b + \frac 1b & \color{#3D99F6} = 4 \\ \left(b + \frac 1b\right)^2 & = 4^2 \\ b^2 + 2 + \frac 1{b^2} & = 16 \\ \implies \color{#3D99F6}b^2 + \frac 1{b^2} & \color{#3D99F6} = 14 \\ \left(b + \frac 1b\right) \left(b^2 + \frac 1{b^2} \right) & = 4 \times 14 \\ b^3 + b + \frac 1b + \frac 1{b^3} & = 56 \\ b^3 + 4 + \frac 1{b^3} & = 56 \\ \implies \color{#3D99F6}b^3 + \frac 1{b^3} & \color{#3D99F6} = 52 \\ \left(b^2 + \frac 1{b^2} \right) \left(b^3 + \frac 1{b^3} \right) & = 14 \times 52 \\ b^5 + b + \frac 1b + \frac 1{b^5} & = 728 \\ b^5 + 4 + \frac 1{b^5} & = 728 \\ \implies \color{#3D99F6}b^5 + \frac 1{b^5} & \color{#3D99F6} = 724 \\ \left(b^3 + \frac 1{b^3} \right)^2 & = 52^2 \\ b^6 + 2 + \frac 1{b^6} & = 2704 \\ \implies \color{#3D99F6}b^6 + \frac 1{b^6} & \color{#3D99F6} = 2702 \end{aligned}

Now, we have:

( b 6 + b 5 ) ( 1 b 11 + 1 ) = 1 b 5 + b 6 + 1 b 6 + b 5 = b 5 + 1 b 5 + b 6 + 1 b 6 = 724 + 2702 = 3426 \begin{aligned} \left(b^6 + b^5 \right)\left(\frac 1{b^{11}} + 1 \right) & = \frac 1{b^5} + b^6 + \frac 1{b^6} + b^5 \\ & = b^5 + \frac 1{b^5} + b^6 + \frac 1{b^6} \\ & = 724 + 2702 \\ & = \boxed{3426} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...